Research on Gender Equality Education Policy in China - Xie, Jingxian (Transactions on Social Science, Education and Humanities Research, 2024)
Since the reform and opening up, China has formulated a series of laws and regulations to guarantee women’s equal right to receive education and pursue gender equality in education. The Fourth Plenary Session of the 19th CPC Central Committee put forward that "the essence of the modernization of state system and state governance system is the modernization of people. The equality and dignity of human nature is the proper meaning of human modernization, which is the consensus of modern civilization. " Gender equality education is the foundation of the development of gender equality, and it is also the top priority of the continuous progress of people’s rights and undertakings. This paper will make a simple analysis from the following aspects: the influence of gender inequality on women and society, the significance and principles of gender equality education, the evaluation of existing policies and suggestions for the future.